Searching for the Way in Life: Yang Zhu’s Theory of Tending Life in Liezi - Zhang, Nan (Literary Studies, 2021)
Known as a Taoist, Yang Zhuw lived in the Warring States Period. In his only transmitted work named ‘Yangzhu’in Liezi, he presented the “tending life” theory which was considered by most scholars as a sort of “hedonism,” “extreme egoism” or “indulgence.” However, the “tending life” theory should not be simply regarded as an avocation of physical enjoyment. First, ‘Yangzhu’ defined Tao（the Way） as a “weak power” which only assists things to “auto-generate” and “self-transform,” so that “tending life” is also a pursuit of the ultimate meaning of Tao. ‘Yangzhu’ further argued that the best way of “tending life” is not to restraint and suppress one’s natural desire, for the realization of “tending life” should be based on the preservation of the body. ‘Yangzhu’ discusses the relationship between the “Ming”(name/reputation) and the “Shi”(Reality), which reveal that the attachment to the “reputation” is the main obstacle of the realization of “tending life.” At last, Yang Zhu proposed that the most ideal life should “roaming as the nature prompt” through a dialectical discussion. Therefore, the theory of “tending life” also reflects a pursuit that to some extent transcends the physical life.